A Thermostat‐Consistent Fully Coupled Molecular Dynamics–Generalized Fluctuating Hydrodynamics Model for Non‐Equilibrium Flows. Issue 2 (20th November 2021) - Liu, Xinjian; Korotkin, Ivan; Rao, Zhonghao; Karabasov, Sergey
Abstract: The thermostat‐consistent fully coupled molecular dynamics–generalized fluctuating hydrodynamics method is developed for non‐equilibrium water flow simulations. The model allows for strong coupling between the atomistic and the continuum hydrodynamics representations of water and shows an improved stability in comparison with the previous formulations of similar multiscale methods. Numerical results are demonstrated for a periodic nano‐scale Poiseuille flow problem with SPC/E water. The computed time‐averaged velocity profiles are compared with the analytical solution, and the thermal velocity fluctuations are well reproduced in comparison with the equilibrium molecular dynamics simulation. Several options to account for the long‐range electrostatics interactions available in GROMACS are incorporated in the model and compared. It is demonstrated that the suggested non‐equilibrium multiscale model is a factor of 4 to 18 faster in comparison with the standard all‐atom equilibrium molecular dynamics model for the same computational domain size. Abstract : A multiscale method is implemented to concurrently couple atomistic and continuum hydrodynamic representations of non‐equilibrium flows. Numerical results for a periodic nano‐scale Poiseuille flow problem with SPC/E water show a 4 to 18‐fold solution acceleration in comparison with all‐atom molecular dynamics simulations in GROMACS. A downloadable copy of the modified GROMACS code for solving non‐equilibrium flow problems is provided.